Transformative Islamic Education: A Philosophical Analysis of the Integration of Islamic Values and Educational Innovation - Bangkit Kurnia; Muhamad Slamet Martin (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
Transformative Islamic education has become an increasingly relevant discourse in response to rapid social change, technological advancement, and the growing complexity of contemporary educational challenges. This study aims to analyze Islamic education from a philosophical perspective by examining how Islamic values can be meaningfully integrated with educational innovation to foster holistic human development. Using a qualitative philosophical approach, this research explores foundational Islamic concepts such as tauhid, akhlaq, ‘ilm, and maslahah as epistemological and axiological bases for educational transformation. The study critically engages with classical and contemporary Islamic educational thought, while also dialoguing with modern educational theories related to innovation, learner-centered pedagogy, and transformative learning. The findings indicate that the integration of Islamic values and educational innovation is not merely a technical adaptation of modern methods, but a value-driven transformation that reorients educational goals toward ethical consciousness, spiritual depth, social responsibility, and intellectual creativity. This integration enables Islamic education to remain faithful to its normative foundations while being responsive to contemporary realities. The study contributes to the development of a conceptual framework for transformative Islamic education that emphasizes philosophical coherence, contextual relevance, and sustainability in educational reform.